An analytical hierarchy process model for the evaluation of the E-government development - Máchová, Renáta (Univerzita Pardubice, 2015)
With the increasing number, variety and effects of modern technologies, e-government needs to define a new evaluation model that fits their requirements and operations. Therefore, this paper presents an example on solving the e-government development evaluation problem using the Analytical Hierarchy Process method. The proposed model consists of criteria identified through the comparison of the selected e-government indices, including the new approaches such as cloud computing, open data, social media, etc. A case study is presented to demonstrate the usefulness of this model to solve multiple criteria decision making problems.
Keywords: AHP; decision making; e-government evaluation; e-government indices; C43; C44; H11; H83; L86